2023
DOI: 10.1021/acsami.3c06336
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Driven Multilevel Non-Volatile Memory with Monolayer MoS2 for Brain-Inspired Artificial Learning

Abstract: The demands of modern electronic components require advanced computing platforms for efficient information processing to realize in-memory operations with a high density of data storage capabilities toward developing alternatives to von Neumann architectures. Herein, we demonstrate the multifunctionality of monolayer MoS 2 memtransistors, which can be used as a high-geared intrinsic transistor at room temperature; however, at a high temperature (>350 K), they exhibit synaptic multilevel memory operations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…The linear output characteristics are observed, indicating the Ohmic contact between Ag and MoS 2 both before and after transfer cases. Such an Ohmic nature of MoS 2 -based FETs using Ag electrodes has also been reported in previous articles. ,, Interestingly, we notice an enhanced gate tuning of drain currents in transferred devices. As shown in Figure (a), the large field-effect modulation from the gate voltage variations in the transferred FET indicates the absence of Fermi-level pinning effects.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The linear output characteristics are observed, indicating the Ohmic contact between Ag and MoS 2 both before and after transfer cases. Such an Ohmic nature of MoS 2 -based FETs using Ag electrodes has also been reported in previous articles. ,, Interestingly, we notice an enhanced gate tuning of drain currents in transferred devices. As shown in Figure (a), the large field-effect modulation from the gate voltage variations in the transferred FET indicates the absence of Fermi-level pinning effects.…”
Section: Resultssupporting
confidence: 90%
“…As shown in Figure (c), before the transfer, we observe a narrow clockwise hysteresis and minimal variation of transfer curves with increasing temperature up to 400 K. However, above 400 K we notice a hysteresis inversion from clockwise to anticlockwise direction and with an increase in the hysteresis window. This inversion in the hysteresis path is also observed in our previous studies which could provide interesting applications in memory and neuromorphic computing. , The hysteresis inversion arises due to additional doping of charge carriers at high temperatures, and the details of such studies can be found elsewhere . Interestingly, as shown in Figure (d), the transistor characteristics of the transferred device do not show temperature-dependent hysteresis inversion, indicating our transfer technique is capable of removing the additional charge doping effects arising from the growth substrate.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Extensive endeavors have been made to pursue electronic devices that mimic the activity similar to biological systems. , Learning and self-optimization remain big challenges for advanced intelligence systems. The need to solve this issue inspires the development of alternative ways to store and process the data simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…[19] However, the incompatibility of organic thin films with the state-of-the-art semiconductor technology hinders their potential in achieving high integration density and data processing-memory capability. [20] 2D layered materials offer significant opportunities for the ultimate realization of next-generation reconfigurable logic-inmemory circuits, owing to their unique physical properties including immunity against short channel effect, [21] high electrical tunability, [22] extraordinary thermal and optical sensitivity, [23,24] and flexible heterojunction integration. [25] Previous works have demonstrated 2D channel polarity dependent logic behavior via developing advanced device architectures, such as splitting gate and dual-gate.…”
Section: Introductionmentioning
confidence: 99%